The Logic of Conformity: Japan's Entry into International Society - TOMOKO T. OKAGAKI (University of Toronto Press, 2013)
The University of Toronto Press, in cooperation with the University of Missouriâ€“St Louis, and the Shibusawa Eiichi Memorial Foundation of Tokyo, is launching an ambitious new series, â€œJapan and Global Society.â€ The volumes in the series will explore how Japan has defi ned its identities and objectives in the larger region of Asia and the Pacifi c, and, at the same time, how the global community has been shaped by Japan and its interactions with other countries. The dual focus on Japan and on global society refl ects the series editorsâ€™ and publishersâ€™ commitment to globalizing national studies. Scholars and readers have become increasingly aware that it makes little sense to treat a country in isolation. All countries are interdependent and shaped by cross-national forces so that mono-national studies, those that examine a countryâ€™s past and present in isolation, are never satisfactory. Such awareness has grown during the last few decades when global, transnational phenomena and forces have gained prominence. In the age of globalization, no country retains complete autonomy or freedom of action. Nations do continue to exist, and they act in pursuit of their respective national interests, which frequently results in international tensions. Financial, social, and educational policies continue to be defi ned domestically, with national communities as units. But transnational economic, environmental, and cultural forces always infringe upon national entities, transforming them in subtle and sometimes even violent ways. Global society, consisting of billions of individuals and their organizations, evolves and shapes national communities even as the latter contributes to defi ning the overall human community.Japan provides a particularly pertinent instance of such interaction, but this series is not limited to studies of that country alone. Indeed, the books published in the series will show that there is little unique about Japan, whose history has been shaped by interactions with China, Korea, the United States, and many other countries. For this reason, we shall publish volumes dealing with countries in the Asia-Pacifi c region and comparing their respective developments and shared destinies. At the same time, it is expected that some studies in the series will transcend national frameworks and discuss more transnational themes, such as humanitarianism, migrations, and diseases, documenting how these phenomena have impacted upon Japan and other countries and how, at the same time, they have contributed to the making of a more interdependent global society.